Improving the physical qualities of students in physical education lessons using fitness classes - Pilova, Svitlana; Panasiuk, Iryna; Galiuza, Sergii; Gruzhevsky, Valery; Bilohur, Vlada (International Journal of Psychosocial Rehabilitation, 2020)
In this article is analyzed fitness classes for improving students' physical qualities. In order to improve the physical qualities of students, there was used the methodology, which is based on the physical exercises' performance with musical accompaniment. This not only positively affected the mental and emotional state of the subjects, but also made it possible to apply an individual approach to each student, depending on his level of physical fitness.